RELATIONSHIP ATTITUDE WITH COMMUNITY COMPLIANCE IN IMPLEMENTING HEALTH PROTOCOL PREVENTION OF COVID 19 IN RW 03 KELURAHAN MANUAN KULON SURABAYA - Ninik Ambar Sari; Dya Sustrami (Universitas Airlangga, 2022)
Introduction: The Covid-19 pandemic has disrupted people's activities when socializing, so many people feel anxious to understand how to reduce the spread of this virus. The majority of people still underestimate and do not comply with the policies launched by the government. The purpose of this study was to analyze attitudes with compliance in the Covid-19 health protocol. Method: This study used a cross sectional approach. Samples were taken by accidental sampling technique as many as 154 people in RW 03 Manukan Kulon Village, Surabaya City. The instrument of attitude and compliance variables used a questionnaire. Data were analyzed using Spearman Rho's test with a significance degree of 0.05. Results: The results showed that there was a relationship between the attitude variable (0.034) and compliance with the Covid-19 health protocol in RW 03, Manukan Kulon Village, Surabaya. Conclusion: The results showed that there was a relationship between attitude and compliance in carrying out health protocols. The suggestion of this research is that it is hoped that community leaders in RW 03 can provide an understanding of health protocols and if necessary, hold the Covid-19 task force again in RW 03 in order to minimize community carelessness in socializing.Keywords: Attitude; Compliance; Health Protocol